1997
DOI: 10.1038/sj.jhh.1000516
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and cardiovascular risk: variations in people of African ancestry and South Asian origin

Abstract: Mortality from coronary heart disease (CHD), stroke and and hypercholesterolaemia are less prevalent in ethnic minority populations in the United Kingdom and unlikely end-stage renal failure are high in South Asian migrants in the UK. This is associated with high prevalence of to explain the differences seen between groups, although each risk factor is likely to contribute to the diabetes and hypertension. These seem to be manifestations of a metabolic syndrome with insulin resistance variation in vascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
121
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(125 citation statements)
references
References 8 publications
4
121
0
Order By: Relevance
“…23 These differences in hypertension complications may be explained by differences in the prevalence of risk factors such as hypercholesterolaemia and cigarette smoking between ethnic groups which are due to the urbanisation and rapid changes in lifestyle in some sub-Saharan African areas and the Middle East. 24 Furthermore, the present study has also shown that the frequency of target organ involvement is a function of both SBP and DBP although the rate of organ damage may vary among individual hypertensives depending on several poorly understood factors, but the presence of target organ damage confers an increased cardiovascular risk to any given level of BP. 25 Our data also point to the positive association of a long duration of hypertension and the number of cigarettes smoked with the presence of any or all types of target organ involvement.…”
Section: Discussionsupporting
confidence: 57%
“…23 These differences in hypertension complications may be explained by differences in the prevalence of risk factors such as hypercholesterolaemia and cigarette smoking between ethnic groups which are due to the urbanisation and rapid changes in lifestyle in some sub-Saharan African areas and the Middle East. 24 Furthermore, the present study has also shown that the frequency of target organ involvement is a function of both SBP and DBP although the rate of organ damage may vary among individual hypertensives depending on several poorly understood factors, but the presence of target organ damage confers an increased cardiovascular risk to any given level of BP. 25 Our data also point to the positive association of a long duration of hypertension and the number of cigarettes smoked with the presence of any or all types of target organ involvement.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, although blacks have a lower rate of ischaemic heart disease, the incidence of end-stage renal disease in blacks with essential hypertension is much higher compared with whites. 83 The lower rate of ischaemic heart disease in blacks may reflect the different pattern of other risk factors as apart from lower PRA, blacks also have a lower fibrinogen, serum cholesterol and triglyceride and a higher high-density lipoprotein (HDL). 83 On the other hand, the reasons for the greater susceptibility to renal damage in blacks with essential hypertension remain to be established but may be a consequence of abnormalities in the renal haemodynamic adaptations to a high salt diet.…”
Section: Functional Significance Of Lower Pra In Blacksmentioning
confidence: 99%
“…83 The lower rate of ischaemic heart disease in blacks may reflect the different pattern of other risk factors as apart from lower PRA, blacks also have a lower fibrinogen, serum cholesterol and triglyceride and a higher high-density lipoprotein (HDL). 83 On the other hand, the reasons for the greater susceptibility to renal damage in blacks with essential hypertension remain to be established but may be a consequence of abnormalities in the renal haemodynamic adaptations to a high salt diet. 84 The lower PRA in blacks and the sluggish response to sodium restriction and diuretics raises the question of the importance of the renin system in the blood pressure response to sodium restriction or to pharmacological treatment in black hypertensives.…”
Section: Functional Significance Of Lower Pra In Blacksmentioning
confidence: 99%
“…1,2 Studies in the United States 3,4 and Britain 5,6 have shown hypertension to be very common and its complications (stroke, heart failure, renal failure) a major cause of morbidity and mortality in black subjects in these countries.…”
Section: Introductionmentioning
confidence: 99%